Dysregulated expression of S100A11 (calgizzarin) in prostate cancer and precursor lesions. - Rehman, I; Azzouzi, A; Cross, S; Deloulme, J; Catto, J; Wylde, N; Larre, S; Champigneuille, J; Hamdy, F (2004)
S100A11 is a calcium-binding protein implicated in a variety of biologic functions such as proliferation and differentiation as well as in cancer. To further understand its role in prostate cancer, we performed immunohistochemistry on a series of benign, premalignant, malignant and metastatic prostate cancer tissues in addition to prostate cancer derived cell lines. In benign prostatic hyperplasia (n=30) and benign tissue adjacent to adenocarcinoma (n=54), S100A11 expression was significantly higher in basal cells compared with in luminal cells (P <0.001). A complete absence of staining was seen in 4/14 (29%) lesions of prostatic intraepithelial neoplasia. The majority of tumors, 39/54 (72%), showed significant overexpression of S100A11 compared with the luminal cells of adjacent benign epithelium (P <0.001), whereas 14/54 (26%) of cases showed an absence of staining. All 4 cases of metastatic cancer showed intense to moderate expression. There was a significant association between S100A11 expression and high pathologic stage (pT3b) versus lower stages (pT2a-3a; P=0.027), but not with tumor Gleason score or prostate-specific antigen levels. LNCaP, PC3, and Du145 cancer cell lines showed intense to moderate S100A11 expression by immunochemistry, which was confirmed by Western blotting and reverse-transcription polymerase chain reaction. A survey of 14 other types of normal tissues arranged on a tissue microarray showed that S100A11 is widely expressed amongst epithelia. Our finding of frequent dysregulated expression of S100A11 in cancer and precursor lesions, together with an association with high histological stage, suggests that S100A11 may be involved in prostate cancer development and progression.